Development of Mobile Durian Farming Application Using Augmented Reality (AR) - Zahrein, Nur 'Atikah; Noraziahtulhidayu Kamarudin, (Applied Information Technology And Computer Science, 2023)
As technology advances, an internet platform is being utilized to gather information regarding durian agriculture, from planting through harvesting. Using a smartphone application, farmers can manage their durian farms using the benefits of information technology. Mobile agriculture applications may be the finest option for enhancing agricultural production in the country. Therefore, the goal of this project is to create MyDurianLand, an Augmented Reality (AR)-based mobile application for durian farming that employs Android technology. MyDurianLand will provide augmented reality (AR) features of the various types of durians, the cultivation steps for durian plants, and tips for growing durian plants. The software should display a 3D model of different types of durians as well as show the user how to cultivate durian plants using 2D animations. Multimedia Development Life Cycle (MDLC) is the development approach for this project, which involves six stages: conceptualization, design, material collection, assembly, testing, and distribution.